.

:





 

110. ( ) :

 


1. )


2¢ + 2 = 1;

æ y ö


) ¢ = ln ç ÷ ;

è x ø

) ¢ = x - + 1 .

 

 


2. )


y2 ¢ + 2x = 1 + x2 ;


 

) ¢ - =


 

2 + 2 ;


 

) (1 - 2)¢ - 2x = 1 + x2 .

 

 


3. )

 

)

)


¢ + x = x2 ;

2 - 4 + 42 ¢ = 0 ;

( - 1)¢ + 2x = 1.


 

 


4. )


2 ¢ + 2 = 1 ;


 

) ¢ =


 

+ 6

2


 

+ 6 ;


 

)

 

5. )


¢ - 3 = .

¢ + = 2 ;


 

) ¢ =


- 2 ;

+


 

) ¢ -


+ 1


 

= .


 


6. )

 

)


¢ - 2 = 2 ;

¢ = + ;


) ¢ - = (2 - 3) .

 


7. )


¢ + - 3 = 0 ;


 

) ¢ =


- 3 ;

+ 3


) 2¢ - = 32 .

 

 


8. )

 

)

 

)

 

 

9. )

 

 

)


¢ = 32 - 2 ;

¢ + - = 0 ;

2 ¢ - 2 = 3 .

 

 

¢ = 1 - 2 ;

2 ¢ + 2 - 2 = 0 ;


 

) ¢ - tg x =


1 .

cos


10. )

 

)


(1 + 2)¢ = + xy2 ;

2 ¢ = 2 + ;


 

) ¢ + 2


= 2 + 2 .


 

1120. - , - :

 


11.


¢ - 2


= ,

4


(1) = 1 .


12.

 

13.


¢ + 43 = 3- × 2 ,

 

¢ + 2ctg x = cos x ,


(0) = 8 .

ç π ÷ = 1.


æ ö


 

 

14.


 

 

2¢ - =


 

3x2

,

y


è 2 ø

 

(1) = 2 .


 

15.


2 ¢ - 2 xy = 2 ,


 

(1) = -1.


 

16.


¢ - 4 = 2 ,


 

(1) = 1 .


 

17.


 

2¢ - 3 = -(202 + 12) 3 ,


(1) = 1 .

2 2


 

18.


¢ - tg x + 2 cos x = 0 ,


 

(0) = 1.


 

19.


2¢ - = - 1 ,

y

2


(2) = 1 .

2


20.


¢ + = 2x- 2


2 ,


(0) = 1.


 

21 23. - :


21.

 

22.

 

23.

24.

 

25.

 

26.


(1 + ) ¢ - 5 × ( ¢)2 = 0 .

(1 - 2 ) ¢ = ¢ .

¢ × tg y = 2(¢)2 .

¢ + y¢ = + 1 .

( ¢)2 + 2 × y¢ = 0 .

¢ - y¢ + 1 = 0 .


 

27.


 

¢ = -2


¢ + 2 .


28.

 

29.

 

30.


1 + ( ¢)2 + × y¢ = 0 .

4 ¢ + 3 y¢ = 4 .

( 2 + 1)¢ + 2y¢ = 3 .


 

31-40. - - , - :

 


31.

 

32.

33.

34.

 

35.

 

36.

 

 

37.


¢ - 4 ¢ + 13 = 262 - 3 ,

¢ + 2 ¢ = -2 (sin x + cos x) ,

¢ + 5 ¢ + 6 = 12 cos 2 ,

¢ + 4 ¢ - 12 = 8 sin 2 ,

¢ + ¢ - 2 = ex (2 + 2) ,

 

¢ - 5 ¢ = 152 + 4 ,

 

 

¢ - 4 ¢ + 5 = ex × ,


(0) = 1,

 

(0) = 0 ,

(0) = 1,

(0) = 0 ,

 

(0) = 2 ,

 

(0) = 1,

 

(0) = 1 ,


¢(0) = 0 .

¢(0) = 0 .

¢(0) = 3 .

¢(0) = 0 .

¢(0) = -1 .

¢(0) = - 2 .

 

¢(0) = 0 .


38.

 

39.

 

40.


¢ - 2 ¢ + = e2 x ( - 1) ,

¢ + 2 ¢ + 5 = 102 - 7 + 8 ,

¢ - 4 ¢ + 3 = 2ex ,


(0) = -2 ,

 

(0) = 0 ,

 

(0) = 2 ,


¢(0) = 0 .

¢(0) = 0 .

¢(0) = 1 .


 

4150. - :

 


 

 

41.


ì dx = 4x + 6 y,

ï dt

í dy


 

 

42.


ì dx = -5x - 4 y,

ï dt

í dy


ï

î dt


= 4x + 2 y .


ï

î dt


= -2x - 3y .


 


 

 

43.


ì dx = 3x + y,

ï dt

í dy


 

 

44.


ì dx = 6x + 3y,

ï dt

í dy


ï

î dt


= 8x + y .


ï

î dt


= -8x - 5y .


 


 

 

45.


ì dx = - x + 5 y,

ï dt

í dy


 

 

46.


ì dx = 3x - 2 y,

ï dt

í dy


ï

î dt


= x + 3y .


ï

î dt


= 2x + 8 y .


 

 

47.


ì dx = -4x - 6 y,

ï dt

í dy


 

 

48.


ì dx = -5x - 8 y,

ï dt

í dy


ï

î dt


= -4x - 2 y .


ï

î dt


= -3x - 3y .


 


 

 

49.


ì dx = - x - 5y,

ï dt

í dy


 

 

50.


ì dx = -7x + 5 y,

ï dt

í dy


ï

î dt


= -7x - 3y .


ï

î dt


= 4x - 8 y .





: 2015-01-25; : 413 | |


:

:


:



© 2015-2020 lektsii.org - -

: 0.027 .